2010
DOI: 10.1111/j.1469-7610.2010.02302.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a parenting program in a high‐risk, multi‐ethnic community: the PALS trial

Abstract: Programs can be organized to be engaging and effective in improving parenting among high-risk, multi-ethnic communities, which is of considerable value. To also be cost-effective in achieving child changes may require a set-up that enables parents to attend more sessions and/or an exclusive focus on children with clinically significant behavior problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…However, the findings are consistent with data from a large predictor study in the USA, 54 a moderator analysis in a large trial of the Family Check-Up in the USA 151 and in a smaller trial in London, UK. 59 Although our data are largely consistent with the modest body of prior work on predictors and moderators, our large pooled study design means that we can have considerably more confidence in this important finding of no moderation by ethnicity. Our finding is also likely to be generalisable across ethnic groups, as families were drawn from a wide range of ethnic groups typical of the UK and Dutch cities where the trials were conducted.…”
Section: Ethnicitysupporting
confidence: 76%
See 2 more Smart Citations
“…However, the findings are consistent with data from a large predictor study in the USA, 54 a moderator analysis in a large trial of the Family Check-Up in the USA 151 and in a smaller trial in London, UK. 59 Although our data are largely consistent with the modest body of prior work on predictors and moderators, our large pooled study design means that we can have considerably more confidence in this important finding of no moderation by ethnicity. Our finding is also likely to be generalisable across ethnic groups, as families were drawn from a wide range of ethnic groups typical of the UK and Dutch cities where the trials were conducted.…”
Section: Ethnicitysupporting
confidence: 76%
“…58 There have been very few studies of outcome differences in parenting trials by ethnicity in the UK or other European countries, or qualitative studies alongside trials. One exception is the trial by Scott et al, 59 conducted in a highly deprived London borough. They found considerable baseline differences in parenting practices by ethnicity, but, intriguingly, no ethnic differences in attendance, or in intervention effects on parenting skills.…”
Section: Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many participant characteristics have been investigated for their relationship to parent participation in prevention and treatment targeting children's problem behavior. Family demographic variables such as minority status, lower socio-economic status, single parent status, and larger family size have been associated with indicators of lower parent participation rates (August et al 2003;Coatsworth et al 2006;Gorman-Smith et al 2002;Kazdin et al 1995;Lavigne et al 2010;Scott et al 2010). Several studies show lower parent participation is associated with higher severity of child behavior problems (August et al 2003;Boxmeyer and Lochman 2006;Gorman-Smith et al 2002;Watt et al 2007), while one study showed that parents participate more when their child has more severe behavior problems (Dumas et al 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Remaining with parental implemented programs but with a different sample -a high-risk, multiethnic group in an inner-city London borough, Scott et al (2010) examined the efficacy of the Primary Age Learning Skills (PALS) trial, an evidence-based parenting group program on parent-child relationship and literacy. The program involved 18 sessions, of which 12 were dedicated to parent-child relationship and six to literacy.…”
mentioning
confidence: 99%